1994
DOI: 10.1002/j.1460-2075.1994.tb06791.x
|View full text |Cite
|
Sign up to set email alerts
|

A new calcium binding glycoprotein family constitutes a major diatom cell wall component.

Abstract: Diatoms possess silica‐based cell walls with species‐specific structures and ornamentations. Silica deposition in diatoms offers a model to study the processes involved in biomineralization. A new wall is produced in a specialized vesicle (silica deposition vesicle, SDV) and secreted. Thus proteins involved in wall biogenesis may remain associated with the mature cell wall. Here it is demonstrated that EDTA treatment removes most of the proteins present in mature cell walls of the marine diatom Cylindrotheca f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
191
1
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(203 citation statements)
references
References 22 publications
4
191
1
7
Order By: Relevance
“…From the two taxa the diatoms and the siliceous sponges, the importance of the organic templates for the formation of their biomineralic skeletons has been well elucidated. The ornate and elaborated diatom frustules are formed onto organic templates (Kröger et al, 1994;Kröger et al, 1997;Kröger et al, 1999;Sumper and Brunner, 2008;Hildebrand et al, 2008), the biosilica-associated peptides (silaffins) and the long-chain polyamines (see Poulsen et al, 2003). Furthermore, it was found that those organic molecules accelerate silica formation from a silicic acid solution in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…From the two taxa the diatoms and the siliceous sponges, the importance of the organic templates for the formation of their biomineralic skeletons has been well elucidated. The ornate and elaborated diatom frustules are formed onto organic templates (Kröger et al, 1994;Kröger et al, 1997;Kröger et al, 1999;Sumper and Brunner, 2008;Hildebrand et al, 2008), the biosilica-associated peptides (silaffins) and the long-chain polyamines (see Poulsen et al, 2003). Furthermore, it was found that those organic molecules accelerate silica formation from a silicic acid solution in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies of the former identified the presence of protein families involved in cell interactions within metazoans, including C-type lectins, cadherins, and fibrinogen (King et al, 2003). In other lineages of microalgae that form colonial structures, such as Volvox carteri, there is supporting evidence for glycoproteins cross-linking within the extracellular matrix of colonies (Hallmann, 2003), as well as serving other important functional roles in cell-cell attachment during colony formation (for example, colony formation in the cyanobacteria Microcystis aerginosa) and as an integral component of cell walls (for example, the diatoms Navicula pelliculosa and Craspedostauros australis) (Chiovitti et al, 2003;Kröger et al, 1994;Zilliges et al, 2008). In this study, environmental isolates of P. antarctica displayed consistent trends in similar protein families (for example, lectins, fibrillins, and glycoproteins), and they were produced at higher levels under elevated iron conditions when strain 1871 was primarily in colonial form.…”
Section: Observation Of An Iron-induced Switch From Single Cells To Cmentioning
confidence: 99%
“…Three families of proteins have been identified in the cell wall of marine diatom C. fusiformis, termed frustulins, pleuralins and silaffins (Pohnert, 2002). Frustulins are a group of calcium-binding glycoproteins being assumed to play a role in cell adhesion to surfaces, gliding of pennate diatoms, and protection against desiccation (Kröger et al, 1994;1996). The pleuralins (HF-extractable www.intechopen.com Learning from Biosilica: Nanostructured Silicas and Their Coatings on Substrates by Programmable Approaches 161 proteins) are highly acidic molecules, comprising a proline-rich region and several repeats of a proline-, serine-, cysteine, aspartate-rich domain (Kröger et al, 1997).…”
Section: Biosilica Formation Mediated With Self-assembled Organic Matrixmentioning
confidence: 99%